Green Hotel as a Competitive Product: A Case Study at 5-Star Hotel in Bali - Astawa, I Ketut; Budarma, I Ketut; Widhari, Cokorda Istri Sri; Mudana, I Gede (Technium Social Sciences Journal, 2020)
Today, tourists tend to choose hotels that consistently implement environmentally friendly practices. In accordance with this phenomenon, the concept of sustainable accommodation needs to apply the principles of environmental conservation, ecology, community empowerment, and the use of local products. Therefore, this study aimed to analyze Green Hotel as a Competitive Product. The problem of this study is “What green aspects do the hotel have that differentiate them from other competitors”? The population was 57 of five stars hotel in Bali that received THK Tourism Award. Meanwhile, 10 percent of the sample was determined by purposive sampling, and the data analysis method used was qualitative descriptive technique. The results showed that the product was developed from an ordinary characteristic to a greener specification. In response to green business practices, 100 per cent stated that adopting the practices can maintain the image of the hotel brand, serve as a competitive advantage, and make the company and employee performance more effective and efficient. Furthermore, the results showed that implementing environmentally friendly business practices are achieved by adopting local wisdom values.